Lista de corales hermatípiros (Anthozoa: Scleractinia; Hydrozoa: Milleporina) a ambos lados del istmo de Panamá - Holst, Irene (Universidad de Costa Rica, 1993)
Fifty eight and nineteen hennatypic scleractinian coral species are reponed for the Caribbean and Facifi.e coasts oC Panamá, respecnvely. Three species of Millepora are reponed for each side of the istlunus. This lisa includes 11 new Caribbean and four new Pacific records of scleractinian species. A new possibly endemic species, Perites coIonensis. is included in the listo The genus Siderastrea is reporled from the Eastem Pacific for the firsa time. Millepora boschmaí (a new spccies presumably extinct) and a l arge solitary individual 01 Den.dregyra cylíndrus were found. Several species are slill undescribed. Taxonomic work is urgently required for determine the diversity of coral. in the regioo befare populatíoos are reduced and management plans are implemented